Genomic resistant determinants of multidrug-resistant Campylobacter spp. isolates in Peru - Schiaffino, Francesca (2024)
Objectives: Antimicrobial resistant (AMR) Campylobacter is a global health threat; however, there is limited information on genomic determinants of resistance in low- and middle-income countries. We evaluated genomic determinants of AMR using a collection of whole genome sequenced Campylobacter jejuni and C. coli isolates from Iquitos, Peru. Methods: Campylobacter isolates from two paediatric cohort studies enriched with isolates that demonstrated resistance to ciprofloxacin and azithromycin were sequenced and mined for AMR determinants. Results: The gyrA mutation leading to the Thr86Ile amino acid change was the only gyrA mutation associated with fluoroquinolone resistance identified. The A2075G mutation in 23S rRNA was present, but three other 23S rRNA mutations previously associated with macrolide resistance were not identified. A resistant-enhancing variant of the cmeABC efflux pump genotype (RE-cmeABC) was identified in 36.1% (35/97) of C. jejuni genomes and 17.9% (12/67) of C. coli genomes. Mutations identified in the CmeR-binding site, an inverted repeat sequence in the cmeABC promoter region that increases expression of the operon, were identified in 24/97 C. jejuni and 14/67 C. coli genomes. The presence of these variants, in addition to RE-cmeABC, was noted in 18 of the 24 C. jejuni and 9 of the 14 C. coli genomes. Conclusions: Both RE-cmeABC and mutations in the CmeR-binding site were strongly associated with the MDR phenotype in C. jejuni and C. coli. This is the first report of RE-cmeABC in Peru and suggests it is a major driver of resistance to the principal therapies used to treat human campylobacteriosis in this setting.